PENGARUH MANAJEMEN LABA, JAMINANDAN UMUR OBLIGASI TERHADAPPERINGKAT OBLIGASI - Caesa Andriyani; Deni Darmawati (Lembaga Penelitian Universitas Trisakti, 2016)
Bond Rating is the first assessment for investor to buy bonds because bonds rating provide information about the possibility company’s debt failure for the issuer evidence.This research aims to provide the effect that earnings management, secure and maturity of bond on bond rating. This research used profitability and leverage as control variable. In addition, this research compared two type measurements of earnings management that are accrual based earning management and real activities earning management. Samples used in this research are all companies listed on the Stock Exchange except the financial sector and has been ranked by the PT. Pefindo by the year 2011-2013. The method of analyses used is logistic regression.The result of this research is (1) Accrual based earning management effect on bond rating. (2) Secure effect on bond rating. (3) Maturity has no effect on bond rating.